Efficient synthesis of a (S)-fluoxetine intermediate using carbonyl reductase coupled with glucose dehydrogenase. (February 2018) - Tang, Yunping; Zhang, Guomei; Wang, Zheng; Liu, Dan; Zhang, Linglu; Zhou, Yafeng; Huang, Ju; Yu, Fangmiao; Yang, Zuisu; Ding, Guofang
Highlights: A newly synthesized CBR gene was expressed in E. coli for (S)-CPPO production. 100 g/L 3-CPP was completely converted to (S)-CPPO with an ee value of 99.6%. It was the highest reported to date for the bio-production of (S)-CPPO. Abstract: (S)-3-chloro-1-phenyl-1-propanol ((S)-CPPO) is an important chiral intermediate predominantly used in the synthesis of the chiral side chain of (S)-fluoxetine. In this study, carbonyl reductase (CBR) from Novosphingobium aromaticivorans was successfully expressed in recombinant E. coli . The enzymatic activity of the recombinant CBR was significantly increased to 1875 U/mL in the fed-batch fermentation in a 10 L fermenter and recombinant CBR was then purified and characterized. By regenerating NADH with glucose dehydrogenase, 100 g/L 3-chloro-1-phenyl-1-propanone (3-CPP) was successfully converted to (S)-CPPO with a conversion of 100% and ee value of 99.6% after 12 h at 30 °C in PBS buffer (pH 7.0), which are the highest reported to date for the bio-production of (S)-CPPO and presented great potential for green production of (S)-CPPO at industrial scale.